Analisis Faktor-faktor yang Mempengaruhi Pendapatan Usaha Mikro: Studi Kasus pada Usaha yang Terdaftar pada Dinas Koperasi dan UMKM di Kota Baubau - Rosnawintang; Saputri, Sista; Tamburaka, Irmawatty Paula (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of business capital, business location, e-commerce and promotion on micro business income in Baubau City. The research sample was 71 business people in Baubau City. This type of research is quantitative research. The analysis method used is multiple linear regression analysis with the Eviews 12 software application tool. Based on the results of the distribution of respondents' answers, it shows that overall, factors including capital, business location, e-commerce, and promotion are considered important by respondents in supporting their business income. Based on the test results, this study shows that: (1) The capital variable has a positive and significant effect; (2) The business location variable has a positive and significant effect; (3) The e-commerce variable has a positive and insignificant effect; (4) The promotion variable has a positive and significant effect; (5) In the hypothesis testing results it was found that all independent variables together had a significant effect on the dependent variable.